Asuhan Keperawatan Pada An.E Dengan Gangguan Sistem Muskuloskeletal : Pre Operasi Fraktur Klavicula Dextra di Ruang Mawar 2 RSUD Dr.Soeselo Kabupaten Tegal - Tri Niar Sari; Ahmad Zakiudin; Sujono Sujono (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2024)
A fracture is a broken bone that is usually caused by trauma or physical force. Upper extremity fractures occur due to traffic accidents, the signs and symptoms caused by fracture sufferers are severe pain, discoloration, swelling, numbness or tingling in the fingers or decreased hand movement (Susanti & Surya Purnama, 2021). The purpose of this writing is to find out and provide nursing care to An.E with musculoskeletal system disorders: pre-operative right clavicle fracture in Rose Room 2 Dr. Soeselo Tegal Regency in accordance with nursing standards. The methods used are descriptive methods and data collection methods. From the case review, it was found that An.E's main complaint was pain. There were three diagnoses found, namely acute pain, anxiety and impaired physical mobility. Interventions are prepared based on the theory of SDKI, SLKI and SIKI as well as on the client's condition and can be implemented.